A QURANIC-BASED APTITUDE ASSESSMENT FOR NEW MUSLIM CONVERTS - Mabrouk, Ahmed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The most important, and perhaps challenging, task that faces new Muslim converts is the acquisition of sufficient Islamic education. Only with such education will their Islamic character develop and would become real contributors to society. The very diverse scientific backgrounds and personal aptitudes of the new converts suggest different methodologies in the way curricula are composed, as well as different approaches for teaching them. In this study, we propose the development of a Quranic-based Aptitude assessment for new Muslim Converts (QAMC-I) as a technique to determine a suitable, semi-customized educational path for each. QAMC-I should indicate whether the concerned candidate has professional, scholarly characteristics that could enable him to specialize in a field of Islamic studies. It should also indicate which field of Islamic studies that a non-specialist would like more and a specialist would excel in. This paper introduces the guiding principles of the proposed QAMC-I. In this work, we introduce a more universal exposition of the underlying principles of cognitive measurement techniques that is more suitable to the universal and analytical nature of the Quran.